Kedudukan Hakim Perempuan Perspektif Abu Hanifah dan Ibn Hazm - Syahfaruddin, Puthut (UIN Sunan Kalijaga Yogyakarta, 2016)
Judge is one of the important professions because it is one of the highest positions in Islam. This position is higher than that of the mufti because the judge's job is not just to pronounce the law but also to impose a sentence that results from the legal decision that must be implemented and obeyed. The purpose of this study is to explain, analyze, and evaluate the conditions and factors behind the differences of opinion between Imams Abu Hanifah and Ibn Hazm regarding the position of women serving as judges and to explain the legal istinbath used by the priests of that school. According to the type of research, this research is categorized as qualitative research (literary). The nature of the research used is descriptive-analysis-comparative, using a socio-historical approach and inductive thinking methods, so this research is expected to produce several useful scientific studies. The results of the author's analysis are the factors behind the difference of opinion between Imam Abu Hanifah and Ibn Hazm and differences in interpreting and understanding the texts. The similarities of opinion between the two regarding the position of female judges are that it is permissible for a woman to serve as a judge, and both of them do not make men an absolute requirement to become judges. Meanwhile, the difference of opinion between them is whether Imam Abu Hanifah limited the authority of female judges to civil matters, in contrast to Ibn Hazm, who allowed women to serve as judges.